Analisis Nilai Perusahaan Sub Sektor Batu Bara yang Terdaftar di Bursa Efek Indonesia - Luthfiyah, Anisa Euri; Utami, Kery (Jurnal Bisnis dan Manajemen, 2022)
This research was conducted in order to examine the effect of capital structure, profitability, and firm size on a firm's value. The research was carried out in the coal sub-sector which was listed on the Indonesia Stock Exchange (IDX) in 2016 to 2020. This type of research was quantitative research with the method of determining the sample used was purposive sampling and the research sample obtained was 16 companies. The data analysis technique used is panel data regression analysis assisted by the Eviews 11 program. The results are obtained, namely profitability and capital structure partially have a significant and positive influence on firm value. While the size of the company has a negative and significant effect on the value of the company.